To optimize the efficacy of bioheat transfer in capacitive hyperthermia : a physical perspective - Jamil, Muhammad (2013)
This paper presents the capacitive hyperthermia from physical perspective focusing on the geometric dimensions as parameters. For this purpose six parameters having three levels each, including two tunable parameters i.e. applied voltage, frequency together with four geometric parameters i.e. size of the tumor, location of the tumor, electrode size and relative position of the electrodes w.r.t tumor were considered for analysis. Taguchi based design of experiments approach was used for the aforementioned six parameters. Using Taguchi's standard L27 orthogonal array, the required results could be obtained employing least number of experiments. For this study temperature was taken as the quality characteristic to be optimized. Furthermore, analysis of variance (ANOVA) was performed to quantify the effect of each parameter on the response variable and results were presented. To deal with the extent of thermal damage to the healthy tissue and tumor, the fraction of tissue experiencing thermal damage was calculated. For this purpose two indices namely treatment index and damage index were formulated. Finally it was concluded that maximum achieved temperature alone does not depict the effectiveness of the treatment. Rather, the combination of the maximum achieved temperature and accompanied thermal damage to the surrounding healthy tissue which should be considered.